Optimized design and performance evaluation of an electric cup-chain potato metering device - Kang, Niu; Xianfa, Fang; Yangchun, Liu; Chengxu, Lü; Yanwei, Yuan (International Journal of Agricultural and Biological Engineering, 2017)
The cup-chain metering device is commonly used in potato planters despite its problems of missing-seeding, double-seeding and ground wheel sliding. A mechanical-electrical design was developed for planters to resolve these problems. A regression experiment was conducted with three factors (chain speed, chain tightening distance and cup tilting) and two indicators (missing-seeding rate and double-seeding rate). Based on the results of regression experiment, a numerical regression model was built and a multi-objective optimization method was used to get an optimal solution. Subsequently, the optimized device was tested in the field. The device design presents a tilting seed cup with a guard plate and an electric control system. The laboratory test showed that the missing-seeding rate increased with the chain speed. It initially decreases and then increases with the chain tightening distance and cup tilting angle. The double-seeding rate declines with chain speed. It increases initially and declines afterward with the chain tightening distance. The optimization resulted in a missing-seeding rate of 4.39% and a double-seeding rate of 8.78% under the parameters of 0.32 m/s seeding speed, 0.94×10-3 m tightening distance, and 12.5° cup tilting angle. The field test demonstrated that electric control instead of ground wheel-driven chain enables fast seeding and precise intra-row seeding distance.Keywords: potato planter, cup-chain metering device, multi-objective optimization, regression methodDOI: 10.3965/j.ijabe.20171002.2547Citation: Niu K, Fang X F, Liu Y C, Lü C X, Yuan Y W. Optimized design and performance evaluation of an electric cup-chain potato metering device. Int J Agric & Biol Eng, 2017; 10(2): 36–43.